I.T. & Organizational Performance; Private Education in Singapore - Ho, Robin (2006)
At the turn of the century, the Singapore Government embarked on a drive to develop Singapore as a ÃÂÃÂ¢ÃÂÃÂÃÂÃÂBoston of the EastÃÂÃÂ¢ÃÂÃÂÃÂÃÂ in a bid to attract regional students and international universities to set up campuses in the country. The primary objective of this report is to provide a general overview into the impact of I.T. on private education providers in Singapore. Despite the widespread availability of I.T. infrastructure in Singapore and the various schemes promoting I.T. provided by the Government, a closer look needs to be taken at the real impact and influence of I.T. investments on the private schools. The premise of this research is based on the ongoing debate posed by the purported I.T. paradox on I.T. investmentsÃÂÃÂ¢ÃÂÃÂÃÂÃÂ potential for impact on firm performance and in particularly, in relation to firm output. Using three Singapore private schools as case-studies, we will attempt to investigate the various impacts of I.T. investments on the schools. However, the study will be reflection of only the tip of the ice-berg as there are almost one thousand registered private schools in Singapore, each with varying levels of academic programs and with varying organizational structures. This report looks in-depth at three of the most common distinct types of private education providers in Singapore; The first is an SME-type private school which provides up to bachelorÃÂÃÂ¢ÃÂÃÂÃÂÃÂs degree program in Design, the second is a Government-Linked Company type which provides overseas Masters in Business Administration (MBA) programs, and the last is a Publicly-listed type of private school which also offers MBA programs, although rare, such schools seem to represent a growing trend. This study makes use of conventional private education measures such as student enrolment numbers, administrative costs as well as teaching quality and customer satisfaction to conduct the study. It explores the returns which these schools had enjoyed as a result of their investments into I.T. and looks at some of the factors which had contributed to the results. The results of the study revealed that the investments in I.T. were driven by different factors and I.T. played similar yet different roles for each school. Whilst I.T. did indeed show a propensity to increase revenue and improve customer experience, I.T. did not necessarily lead to a lowering of operational costs and the implementation of ÃÂÃÂ¢ÃÂÃÂÃÂÃÂirrelevantÃÂÃÂ¢ÃÂÃÂÃÂÃÂ I.T. can backfire, leading to customer dissatisfaction.